2012
DOI: 10.1007/s11060-012-0847-y
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient histogram analysis stratifies progression-free and overall survival in patients with recurrent GBM treated with bevacizumab: a multi-center study

Abstract: We have tested the predictive value of apparent diffusion coefficient (ADC) histogram analysis in stratifying progression-free survival (PFS) and overall survival (OS) in bevacizumab-treated patients with recurrent glioblastoma multiforme (GBM) from the multi-center BRAIN study. Available MRI’s from patients enrolled in the BRAIN study (n = 97) were examined by generating ADC histograms from areas of enhancing tumor on T1 weighted post-contrast images fitted to a two normal distribution mixture curve. ADC clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
120
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 23 publications
10
120
2
1
Order By: Relevance
“…Conversely, patients with ADCL Յ 1.2 m 2 /ms do not appear to benefit from bevacizumab therapy at recurrence, and it may, in fact, perform slightly worse than standard therapies (Fig 3C). These current results, along with results from previous studies, 9,19 support the use of ADC histogram analysis in recurrent GBM to guide the use of bevacizumab in second-line therapy. The precise mechanism and biologic correlates for survival differences based on ADC histogram analysis remain controversial.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Conversely, patients with ADCL Յ 1.2 m 2 /ms do not appear to benefit from bevacizumab therapy at recurrence, and it may, in fact, perform slightly worse than standard therapies (Fig 3C). These current results, along with results from previous studies, 9,19 support the use of ADC histogram analysis in recurrent GBM to guide the use of bevacizumab in second-line therapy. The precise mechanism and biologic correlates for survival differences based on ADC histogram analysis remain controversial.…”
Section: Discussionsupporting
confidence: 80%
“…Although previous studies have demonstrated the ability of pretreatment ADC histogram analysis to predict recurrent GBM response to bevacizumab in both single- 9 and multicenter clinical trials, 19 a significant question remained as to whether this type of analysis is a predictive biomarker, specific to bevacizumab therapy, or whether it is a prognostic biomarker independent of the type of treatment. A previous study 9 did suggest that pretreatment ADC histogram analysis could predict response to recurrent GBM treated with bevacizumab, but not in matched patients with recurrent GBM treated with a non-VEGF-targeted investigative antiangiogenic agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 These results support the findings, in a group of 39 highgrade gliomas, previously published by Hamstra et al, 27 who reported that tumor assessment based on functional diffusion maps provides an early biomarker for response, time to progression, and overall survival in patients in malignant gliomas. Recently, Pope et al 28,29 demon- Note:--indicates that at the end of follow-up, patients had not reached median overall survival. strated the relevance of ADC values in the management of gliomas.…”
Section: Discussionmentioning
confidence: 99%